Steps, Implementation and Importance of Quality Management in Diagnostic Laboratories with Special Emphasis on Coronavirus Disease-2019 - Pawar, Shailesh D. (Indian J Med Microbiol, 2020)
A well-established and functional quality management system is an integral part of any diagnostic laboratory. It assures the reliability and standards of the laboratory function. A pandemic situation such as that caused by the influenza H1N1 2009 virus or the recent severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) increases the demands on the public health system, and the need to build, upgrade and expand the number of diagnostic laboratories. The Coronavirus disease-19 (COVID-19) pandemic caused by the SARS-CoV-2 unleashed a public health emergency of an unprecedented scale. The need has been highlighted for the accreditation of tests relating to COVID-19 by the National Accreditation Board for Testing and Calibration Laboratories (NABL) or any agencies approved by the World Health Organization (WHO) or Indian Council of Medical Research. The implementation of quality system in diagnostic laboratories would ensure accurate, reliable and efficient test results at par with the international standards. The functional aspects of a laboratory such as a well-defined organogram, standard operating procedures, good laboratory practices, quality controls, human resources, equipment management, reagents, inventory of records, proper communication need to be addressed to assure quality. Biosafety considerations should include the guidelines laid out by the WHO, the Institutional Biosafety Committee and the Department of Biotechnology, Government of India for carrying out diagnostic work in the laboratory. Currently, there are 1922 laboratories, operational for COVID-19 diagnosis in India. Considering the urgency of testing, the NABL has expedited the process of accreditation and issued accreditation to 818 laboratories. The adherence to the practicable aspects of quality described in this article would help in establishing quality in COVID-19 testing laboratories.